RELEVANSI KURIKULUM 2013 DAN EFIKASI DIRI DALAM MEMPERSIAPKAN TUNTUTAN PENDIDIKAN ABAD 21 - Yeni Rakhmawati; Handara Tri Elitasari; Irma Yulianti Budi Safitri; Muhammad Asip (Universitas Muhammadiyah Purwokerto, 2023)
The implementation of the 2013 curriculum is to develop character and equip learners in the era of global competition. One of the important competencies is self-efficacy. The purpose of the research is to find a hypothesis that self-efficacy can serve as the basis to meet the demands of the 21st century and self-efficacy can develop through the curriculum 2013. The research method is literature study using research and book journals. The results of the self-efficacy study equip students to foster confidence in him that he is able to act and solve problems. Self-efficacy can be developed with a scientific approach that includes observing, questioning, trying, declaring, and communicating. The influence of self-efficacy in the individual is enormous, the individual can plan goals and design the process and there is self-confidence to achieve its goals. Long-term goal is to choose a career according to ability and belief so that can compete in the 21st century.